COMMUNITY PARTICIPATION IN MAINTAINING COMPLIANCE WITH ISLAMIC VALUES IN BUKIT TINGGI TOURIST DESTINATIONS (International Conference on Social and Islamic Studies, 2021)
Madura is a small island whose people are famous for their very strong religiosity. Islamic values are maintained very well in almost all aspects of their lives, including intourism. The purpose of this study is to find out how community involvement helps maintain adherence to Islamic values in Bukit Tinggi tourist destinations. Research methods use a qualitative approach. The data was obtained through interviews, and observations and analyzed with Miles and Huberman's Interactive Analysis Model. The results of this study showed that the public voluntarily participated in monitoring the behavior of tourists, reprimanding tourists if they did things that were not under Islamic teachings, and also processed them to the Village Chief if the actions of these tourists had exceeded the limit. This research concludes that involving the community in maintaining compliance with Shariah is very helpful for tourism managers to always keep these tourist destinations from unwanted things and violate religious rules. The results of this study contribute that managers can join hands with the community in the management of tourism including in maintaining the value of Islam in this tourist destination.